Small-bowel capsule endoscopy and device-assisted enteroscopy for diagnosis and treatment of small-bowel disorders: European Society of Gastrointestinal Endoscopy (ESGE) Technical Review - Rondonotti, Emanuele; Spada, Cristiano; Adler, Samuel; May, Andrea; Despott, Edward J.; Koulaouzidis, Anastasios; Panter, Simon; Domagk, Dirk; Fernandez-Urien, Ignacio; Rahmi, Gabriel; Riccioni, Maria Elena; van Hooft, Jeanin E.; Hassan, Cesare; Pennazio, Marco (Endoscopy, 2018)
Small-bowel capsule endoscopy (SBCE)1 ESGE recommends that prior to SBCE patients ingest a purgative (2 L of polyethylene glycol [PEG]) for better visualization.Strong recommendation, high quality evidence.However, the optimal timing for taking purgatives is yet to be established.2 ESGE recommends that SBCE should be performed as an outpatient procedure if possible, since completion rates are higher in outpatients than in inpatients.Strong recommendation, moderate quality evidence.3 ESGE recommends that patients with pacemakers can safely undergo SBCE without special precautions.Strong recommendation, low quality evidence.4 ESGE suggests that SBCE can also be safely performed in patients with implantable cardioverter defibrillators and left ventricular assist devices.Weak recommendation, low quality evidence.5 ESGE recommends the acceptance of qualified nurses and trained technicians as prereaders of capsule endoscopy studies as their competency in identifying pathology is similar to that of medically qualified readers. The responsibility of establishing a diagnosis must however remain with the attending physician.Strong recommendation, moderate quality evidence.6 ESGE recommends observation in cases of asymptomatic capsule retention.Strong recommendation, moderate quality evidence.In cases where capsule retrieval is indicated, ESGE recommends the use of device-assisted enteroscopy as the method of choice.Strong recommendation, moderate quality evidence.Device-assisted enteroscopy (DAE)1 ESGE recommends performing diagnostic DAE as a day-case procedure in patients without significant underlying co-morbidities; in patients with co-morbidities and/or those undergoing a therapeutic procedure, an inpatient stay is recommended.Strong recommendation, low quality evidenceThe choice between different settings also depends on sedation protocols.Strong recommendation, low quality evidence.2 ESGE suggests that conscious sedation, deep sedation, and general anesthesia are all acceptable alternatives: the choice between them should be governed by procedure complexity, clinical factors, and local organizational protocols.Weak recommendation, low quality evidence.3 ESGE recommends that the findings of previous diagnostic investigations should guide the choice of insertion route.Strong recommendation, moderate quality evidence.If the location of the small-bowel lesion is unknown or uncertain, ESGE recommends that the antegrade route should be generally preferred.Strong recommendation, low quality evidence.In the setting of massive overt bleeding, ESGE recommends an initial antegrade approach.Strong recommendation, low quality evidence.4 ESGE recommends that, for balloon-assisted enteroscopy (i. e., single-balloon enteroscopy [SBE] and double-balloon enteroscopy [DBE]), small-bowel insertion depth should be estimated by counting net advancement of the enteroscope during the insertion phase, with confirmation of this estimate during withdrawal.Strong recommendation, low quality evidence.ESGE recommends that, for spiral enteroscopy, insertion depth should be estimated during withdrawal.Strong recommendation, moderate quality evidence. Since the calculated insertion depth is only a rough estimate, ESGE recommends placing a tattoo to mark the identified lesion and/or the deepest point of insertion.Strong recommendation, low quality evidence.5 ESGE recommends that all endoscopic therapeutic procedures can be undertaken at the time of DAE.Strong recommendation, moderate quality evidence.Moreover, when therapeutic interventions are performed, additional specific safety measures are needed to prevent complications.Strong recommendation, high quality evidence.